2020
DOI: 10.1097/jte.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Mental and Physical Health Behaviors of Doctor of Physical Therapy Students

Abstract: Introduction. High incidences of mental health issues in the undergraduate and graduate students are reported nationwide. The purpose of this study was to assess the Doctor of Physical Therapy (DPT) students' depression, anxiety, and stress levels using the 21-item Depression, Anxiety, and Stress Scale (DASS-21) to investigate how mental and physical behaviors correlate with DPT students' mental health and to identify the coping strategies of DPT students to guide the intervention strategies of PT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 28 publications
2
29
3
Order By: Relevance
“…These challenges can be overwhelming and are often layered on already high levels of depression, anxiety, and stress. 1-5 In response to the increasing evidence of mental health concerns in students, PT educators are exploring ways to support student well-being and promote professional growth. 6-8…”
Section: Background and Purposementioning
confidence: 99%
“…These challenges can be overwhelming and are often layered on already high levels of depression, anxiety, and stress. 1-5 In response to the increasing evidence of mental health concerns in students, PT educators are exploring ways to support student well-being and promote professional growth. 6-8…”
Section: Background and Purposementioning
confidence: 99%
“…2 ese stressors in combination with evidence that has shown significant impact of mental illness on critical executive functioning skills 13,14 make DPT cohorts a population of concern. Although there are very limited studies demonstrating current levels of suicidal ideation in DPTstudents, a study of DPT students by Ellison et al 15 found it to be as high as 7%. e same study also found moderate to severe levels of stress, anxiety, and depression be significant (19%, 25%, and 12%, respectively).…”
Section: Review Of Literaturementioning
confidence: 99%
“…19 Many educational programs have taken up the charge as evidenced by recent publications related to the health and wellness of student PTs. 3,4 However, despite high levels of anxiety and stress, most DPT students successfully complete their educational program, pass the National Physical erapy Examination, 20 and proceed to clinical practice. 1 e Commission on Accreditation in Physical erapy Education (CAPTE) reported an average graduation rate ranging between 90.0% and 96.0% between 2011 and 2019 and an employment rate average of 99.0% between 2011 and 2020.…”
Section: Introductionmentioning
confidence: 99%
“…19 Many educational programs have taken up the charge as evidenced by recent publications related to the health and wellness of student PTs. 3,4…”
Section: Introductionmentioning
confidence: 99%